2016
DOI: 10.1021/acs.jproteome.6b00386
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic HLA-DR-Presented Self-Peptides Identified Directly from Clinical Samples of Synovial Tissue, Synovial Fluid, or Peripheral Blood in Patients with Rheumatoid Arthritis or Lyme Arthritis

Abstract: HLA-DR-molecules are highly expressed in synovial tissue (ST), the target of the immune response in chronic inflammatory forms of arthritis. Here, we used LC-MS/MS to identify HLA-DR-presented self-peptides in cells taken directly from clinical samples: ST, synovial fluid mononuclear cells (SFMC), or peripheral blood mononuclear cells (PBMC) from five patients with rheumatoid arthritis (RA) and eight with Lyme arthritis (LA). We identified 1,593 non-redundant HLA-DR-presented peptides, derived from 870 source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 75 publications
(209 reference statements)
4
47
0
Order By: Relevance
“…Based on an analysis of HLA‐DR‐presented peptides in LA synovial tissue (Wang et al, ), we previously identified four LA‐associated autoantigens: EC growth factor, matrix metalloproteinase‐10, apolipoprotein B‐100, and annexin A2 (Crowley et al, ; Crowley et al, ; Drouin et al, ; Pianta et al, ). These four self‐proteins are abundant in postinfectious LA synovial tissue and are involved in tissue damage and/or wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an analysis of HLA‐DR‐presented peptides in LA synovial tissue (Wang et al, ), we previously identified four LA‐associated autoantigens: EC growth factor, matrix metalloproteinase‐10, apolipoprotein B‐100, and annexin A2 (Crowley et al, ; Crowley et al, ; Drouin et al, ; Pianta et al, ). These four self‐proteins are abundant in postinfectious LA synovial tissue and are involved in tissue damage and/or wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the methods for the isolation and identification of HLA-DR-presented peptides is given in our previous publications (19,20). In the current study, all nonre-jci.org…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study (20), we identified HLA-DR-presented peptides in synovial tissue, SFMCs, and PBMCs from 5 patients with RA using LC-MS/MS, and the immunogenicity of the peptides was determined using patients' samples in enzyme-linked immunospot (ELISpot) assays. The findings from 1 patient (referred to here as RA1) were of particular interest.…”
Section: Identification Of Naturally Presented Hla-dr Peptides (T Celmentioning
confidence: 99%
See 2 more Smart Citations